Konsep Hadhanah dalam Hukum Islam dan Implementasinya dalam Kompilasi Hukum Islam di Indonesia - Iqbal Pinayungan Munthe; Nursania Dasopang (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the concept of hadhanah within Islamic law and its implementation in the Indonesian Compilation of Islamic Law through a normative–doctrinal library research design. The analysis positions hadhanah as a normative construct shaped by authoritative texts, juristic interpretations, and state legal institutionalization. By synthesizing classical fiqh doctrines, contemporary Islamic legal scholarship, and statutory norms, the study reveals that Islamic jurisprudence offers plural and flexible approaches to child custody, primarily oriented toward the protection and welfare of the child. The codification of hadhanah in the Compilation of Islamic Law represents a pragmatic effort to unify diverse doctrines into an operational legal framework that ensures legal certainty while retaining maslahat-oriented reasoning. Furthermore, the study finds that judicial practice in religious courts demonstrates a dynamic interaction between codified norms and social realities, where judicial discretion and contextual considerations play a decisive role. These findings indicate that the effectiveness of hadhanah depends not only on normative formulation but also on interpretative adaptability within legal institutions. The study contributes theoretically by clarifying the transformation of hadhanah from juristic doctrine to positive law and methodologically by offering a replicable framework for normative legal analysis in Islamic family law.